Synthetic reactions driven by electron-donor–acceptor (EDA) complexes - Yang, Zhonglie; Liu, Yutong; Cao, Kun; Zhang, Xiaobin; Jiang, Hezhong; Li, Jiahong (Beilstein Journal of Organic Chemistry, 2021)
The reversible, weak ground-state aggregate formed by dipole–dipole interactions between an electron donor and an electron acceptor is referred to as an electron-donor–acceptor (EDA) complex. Generally, upon light irradiation, the EDA complex turns into the excited state, causing an electron transfer to give radicals and to initiate subsequent reactions. Besides light as an external energy source, reactions involving the participation of EDA complexes are mild, obviating transition metal catalysts or photosensitizers in the majority of cases and are in line with the theme of green chemistry. This review discusses the synthetic reactions concerned with EDA complexes as well as the mechanisms that have been shown over the past five years.
Keywords: EDA complex; electron acceptor; electron donor; radical; visible light